Pendidikan Anak Pada Kisah Ibu Tunggal Dalam Al-Qur'an - Chaer, Moh. Toriqul; Wahyuna, Azizunisak Hidayati (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article discusses the education of single mother children in the Qur'an. The research uses a literature study, with a subjective hermeneutic approach. From the results of the study, found: first, the education of children in the story of a single mother in the Qur'an consists of two stages, namely prenatal and postnatal education. Second, the education of children in the story of a single mother follows the stages of child development psychology. Starting from the prenatal phase, covering the spiritual and physical education of children to the postnatal phase, in the form of aspects of education, supervision and responsibility of the child to a single mother. Third, children's education in the story of a single mother is found in faith, spiritual and emotional education. The education of children in single mothers is carried out holistically, not partially and not mechanically